PENTINGNYA STRATEGI DAN PENGENDALIAN PADA PENGELOLAAN KEUANGAN PADA SMK DARUR ROJA DEPOK JAWA BARAT - Kusumawardhany, Susi Sih; Shanti , Yunita Kurnia; Sudarmadi , Sudarmadi (PUAN INDONESIA, 2025)
The financial management is one of the important aspects in achieving the goals of education in schools through financial management strategies and controls to ensure that the available resources can be used optimally. Objective: to know the financial management strategy of SMK Darur Roja Depok; to know the role of internal control in maintaining accountability and efficiency in the use of school funds of SMK Darur Roja Depok. Metode: The implementing of PKM activities is carried out by means of discussions and presentation of material related to strategies and control of financial management in the School. Results: The implementation of the activity informed that SMK Darur Roja has a good strategy in managing and controlling school finances, which is obtained from several sources and carried out systematically. Conclusion: SMK Darur Roja Depok has a good financial management strategy; SMK Darur Roja Depok has implemented internal control functions to maintain accountability and efficiency in the use of school funds.